Photocatalytic deodorization additive composition, precursor composition of acrylonitrile polymer material and application of precursor composition
By using a photodeodorization catalyst containing TiO2, WO3, MoO3 and SiO2 in the acrylonitrile polymer material and using a specific preparation method, the problems of poor odorization effect and poor drafting performance in the prior art are solved, and the problem of poor odorization effect and poor drafting performance in the prior art is achieved. Better deodorization effect and material properties.
Patent Information
- Application Number
- CN202411649717.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-02-21
AI Technical Summary
Existing photodeodorizing catalysts exhibit poor deodorizing effects and/or poor drafting properties of the material in acrylonitrile polymer materials.
The photodeodorization catalyst containing TiO2, photocatalytic active metal oxides (such as WO3 or MoO3) and SiO2 is used, and the catalyst is improved by specific preparation methods, including mixing of reaction raw materials, hydrolysis reaction, sealed heat treatment and calcining steps. performance.
The deodorization effect of the photodeodorization catalyst and the drafting performance of the acrylonitrile polymer material are significantly improved, and the service life of the catalyst is extended.
Smart Images

Figure BDA0005140585840000031 
Figure BDA0005140585840000032 
Figure BDA0005140585840000041
Abstract
Description
[0001] This application is a divisional application of the original application. The original application is: Invention Name - Photodeodorizing catalyst, preparation method and application thereof, application number - 202211622684X, application date - 2022.12.16. Technical Field
[0002] The present invention relates to a photocatalytic deodorizing additive composition, a method for preparing the photocatalytic deodorizing additive composition, a precursor composition of an acrylonitrile polymer material, an application of the photocatalytic deodorizing additive composition or the precursor composition of an acrylonitrile polymer material, and a spinning production method for acrylic fibers. Background Art
[0003] Photocatalysts, also known as photocatalysts, refer to compounds that can accelerate the process of chemical reactions under light irradiation. The essence of photocatalytic reactions is to convert solar energy into the energy required for chemical reactions. TiO2 is a transition metal semiconductor photocatalyst, which not only has good biocompatibility and high chemical stability. However, the band gap of TiO2 is large, the band gap is 3.2eV, and the light response range is narrow. It can only be excited by about 5% of the ultraviolet light in sunlight. Therefore, the promotion and use of TiO2 is subject to certain restrictions. The band gap of WO3 is narrow, about 2.5-2.8eV, and the light response range is wide, but tungsten trioxide itself has certain limitations. The reduction ability of the photogenerated electrons it produces is poor, which reduces the photocatalytic efficiency of tungsten trioxide. The heterojunction formed by the WO3 / TiO2 composite photocatalyst can promote the generation of more and effective photogenerated electrons-holes, can utilize more visible light bands, and improve the utilization rate of solar energy.
[0004] Photo-deodorizing catalysts can be added during the fabric finishing process. The advantage of this method is that the photocatalytic deodorizing performance is excellent in the early stage. However, due to the susceptibility to long-term external friction and washing, the photocatalyst on the surface of the fabric is easy to fall off, causing the deodorizing performance to decline significantly with the use of the fabric.
[0005] The photo-deodorizing catalyst can be added to the spinning solution for spinning, so that the fiber has the function of photocatalytic deodorization. After such fibers are made into various fabrics, the fabrics also have the function of photocatalytic deodorization. However, due to the large interface stress between the composite photocatalyst and the fiber matrix material, the mechanical properties of the fiber deteriorate. How to slow down the trend of deterioration of the mechanical properties of the fiber or even completely overcome this defect is one of the goals pursued in the field of chemical fiber deodorization. Furthermore, the deodorization effect of the photo-deodorizing catalyst in the prior art needs to be improved. Summary of the invention
[0006] One of the technical problems to be solved by the present invention is that the photocatalytic deodorization catalyst of the prior art has poor photocatalytic deodorization effect when added to acrylonitrile polymer materials and / or the material has poor drawing performance (small drawing strength and elongation at break), and a new photodeodorization catalyst is provided, which has better deodorization effect and / or the acrylonitrile polymer material added with the catalyst has better drawing performance.
[0007] To solve one of the above technical problems, the technical solution of the present invention is:
[0008] The light deodorizing catalyst comprises the following components by weight:
[0009] The first component: 100 parts; the second component: part a; the third component: part b;
[0010] The first component is TiO2, the second component is a photocatalytically active metal oxide, and the third component is SiO2;
[0011] Among them, a=0~10, b=0~0.5, and a+b≠0.
[0012] In the present invention, the effect of the present invention can be achieved regardless of whether the second component is added or not, but from the perspective of improving the photocatalytic deodorization effect of the photodeodorization catalyst, those skilled in the art can select photocatalytically active metal oxides known in the art. Since the addition of the second component is not the key to the present invention, when the second component is used, the second component is only WO3 or MoO3 as an example.
[0013] We also found that when the second component includes WO3 and MoO3 at the same time, WO3 and MoO3 have a synergistic effect in the photocatalytic deodorization effect. At this time, there is no special restriction on the mutual ratio of WO3 and MoO3, and comparable synergistic effects can be achieved, but the weight ratio of MoO3 to WO3 is preferably 0.05-1, for example but not limited to the weight ratio of MoO3 to WO3 is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc., and the weight ratio of MoO3 to WO3 is more preferably 0.1-0.5. Only for comparison, when MoO3 and WO3 are used simultaneously in the embodiment of the present invention, the weight ratio of MoO3 to WO3 is generally 0.25.
[0014] The photo-deodorizing catalyst of the present invention, because it contains the third component SiO2, obviously suppresses the tendency of the tensile strength of the acrylonitrile polymer material to deteriorate due to the addition of the photocatalyst.
[0015] By way of non-limiting example, a is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, etc.
[0016] By way of non-limiting example, b is 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, etc.
[0017] The second technical problem to be solved by the present invention is the preparation method of the above-mentioned photo-deodorizing catalyst.
[0018] To solve the second technical problem, the technical solution of the present invention is as follows:
[0019] The method for preparing the photo-deodorizing catalyst described in any one of the photo-deodorizing catalyst technical solutions of one of the above technical problems comprises the following steps:
[0020] (1) obtaining a reaction raw material mixture;
[0021] The reaction raw material mixture contains: a Ti source, a photocatalytically active metal source and / or a Si source, water, an optional quaternary ammonium compound, and a pH regulator for adjusting the reaction raw material mixture to a pH of 2 to 6; the Ti source is calculated as TiO2, the photocatalytically active metal source is calculated as its oxide, the photocatalytically active metal source is expressed as its oxide as MOx, the Si source is calculated as SiO2, the quaternary ammonium compound is expressed as T, and by weight, in the reaction raw material mixture: MOx / TiO2=a; SiO2 / TiO2=b; water / (TiO2+SiO2)=0.6-20; T / TiO2=0-5;
[0022] (2) subjecting the reaction raw material mixture to a hydrolysis reaction under stirring;
[0023] (3) Closed heat treatment;
[0024] (4) Calcination
[0025] We found that the use of quaternary ammonium compounds can provide a photodeodorizing catalyst with better deodorizing effect.
[0026] In the above-mentioned technical solution of the preparation method, the Ti source described in step (1) is preferably titanate.
[0027] In the above-mentioned preparation method technical solution, the titanate preferably conforms to the following formula 1:
[0028]
[0029] Wherein, R1-R4 are independently C1-C5 alkyl groups; for example, but not limited to, R1-R4 are independently C1 alkyl groups, C2 alkyl groups, C3 alkyl groups, C4 alkyl groups, and C5 alkyl groups. As non-limiting examples of specific titanates, the titanate may be (tetra)methyl titanate, (tetra)ethyl titanate, (tetra)n-propyl titanate, (tetra)isopropyl titanate, (tetra)n-butyl titanate, (tetra)isobutyl titanate, (tetra)tert-butyl titanate, (tetra)n-pentyl titanate, (tetra)isopentyl titanate, etc. or mixtures thereof. For comparison only, the titanate in the embodiments and comparative examples generally uses (tetra)n-butyl titanate.
[0030] In the above preparation method technical scheme, only as an example, the photocatalytically active metal source in step (1) is a W source and / or a Mo source, and it is further preferred that the W source is ammonium tungstate (molecular formula (NH4) 10 W 12 O 41 ·XH2O) or ammonium metatungstate (molecular formula is (NH4)6H2W 12 O 40 ·XH2O) and / or further preferably the Mo source is ammonium dimolybdate ((NH4)2Mo2O7·4H2O), ammonium tetramolybdate ((NH4)2Mo4O 13 2H2O) or ammonium heptamolybdate ((NH4)6Mo7O 24 ·4H2O), among which ammonium heptamolybdate has better water solubility, and ammonium heptamolybdate is preferred from this aspect. When the W source is used in step (1), the W source is measured in the form of oxides of WO3, and when the Mo source is used in step (1), the Mo source is measured in the form of oxides of MoO3.
[0031] In the above-mentioned technical solution of the preparation method, it is preferred that the Si source described in step (1) is a silicate.
[0032] In the above-mentioned preparation method technical scheme, the silicate preferably conforms to the following formula 2:
[0033]
[0034] Wherein, R5-R8 are independently C1-C5 alkyl. For example, but not limited to, R5-R8 are independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl. As non-limiting examples of specific silicates, silicates can be (tetra) methyl silicate, (tetra) ethyl silicate, (tetra) n-propyl silicate, (tetra) isopropyl silicate, (tetra) n-butyl silicate, (tetra) isobutyl silicate, (tetra) tert-butyl silicate, etc. or mixtures thereof. For comparison only, (tetra) ethyl silicate is generally used in the embodiments and comparative examples.
[0035] In the above-mentioned preparation method technical scheme, the quaternary ammonium compound described in step (1) preferably contains a quaternary ammonium ion conforming to the following formula 3:
[0036]
[0037] Among them, R9~R 12 is independently a C1-C5 alkyl group, such as but not limited to R9-R 12 The quaternary ammonium compound may be a quaternary ammonium salt or a quaternary ammonium alkali. The quaternary ammonium alkali also becomes a quaternary ammonium salt when the pH value is 2 to 6, which increases the amount of the pH regulator. In addition, since the quaternary ammonium alkali is usually prepared from a quaternary ammonium salt as a raw material, the cost of the quaternary ammonium alkali is higher than that of the quaternary ammonium salt. Therefore, the quaternary ammonium salt is preferred. Any quaternary ammonium salt that can dissolve in water at a pH value of 2 to 6 may be used, such as quaternary ammonium sulfate, quaternary ammonium chloride, quaternary ammonium bromide, etc. However, in order to reduce the amount of impurities in the catalyst product caused by the quaternary ammonium anion part or to save the cost of removing impurities, the preferred step (1) is preferably quaternary ammonium chloride or quaternary ammonium bromide. As a non-limiting example, the quaternary ammonium compound in step (1) can be at least one selected from the group consisting of tetramethylammonium bromide, tetramethylammonium chloride, tetramethylammonium hydroxide, tetraethylammonium bromide, tetraethylammonium chloride, tetraethylammonium hydroxide, tetra-n-propylammonium bromide, tetra-n-propylammonium chloride, tetra-n-propylammonium hydroxide, etc. For comparison only, tetraethylammonium bromide is generally used in the specific embodiments of the present invention.
[0038] In the above preparation method technical scheme, as a non-limiting example, after using the pH adjuster, the pH of the reaction raw material mixture in step (1) is 2.5, 3, 3.5, 4, 4.5, 5, 5.5, etc. For the convenience of comparison, in the specific implementation mode, the pH value of the mixture is 5.
[0039] In the above-mentioned technical scheme of the preparation method, in step (1), any substance that can adjust the pH of the reaction raw material mixture to 2 to 6 can be used as a pH adjuster, such as sulfuric acid, phosphoric acid, nitric acid and acetic acid, but preferably, those acids whose anion part can volatilize or decompose and volatilize under roasting conditions can be used, so as to reduce impurities in the final catalyst product or save the cost of removing impurities. For example, the pH adjuster in step (1) is acetic acid, hydrochloric acid or nitric acid. Since acetic acid is weak in acidity, when the pH is adjusted to below 3, the amount is too large and uneconomical; hydrochloric acid and nitric acid are strong acids, so when the pH is adjusted to below 3, hydrochloric acid or nitric acid is preferred. However, hydrochloric acid and nitric acid are more corrosive than acetic acid. When the pH is adjusted to 4 to 6, acetic acid is preferred from the perspective of operating environment health and safety. Only for comparison, the pH adjusters used in the specific implementation method are all glacial acetic acid.
[0040] In the above preparation method technical scheme, as a non-limiting example, water / (TiO2+SiO2) is 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc. More preferably, 1 to 10.
[0041] In the above-mentioned preparation method technical scheme, as non-limiting examples, T / TiO2 is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, etc. For comparison only, in the case of using quaternary ammonium compounds in the specific implementation mode, T / TiO2 is 0.1.
[0042] In the above-mentioned technical solution of the preparation method, the reaction raw material mixture in step (1) can be obtained by a method comprising the following steps:
[0043] (i) obtaining a solution I, wherein the solution I contains a titanate and, if necessary, a silicate;
[0044] (ii) obtaining an aqueous solution II containing a photocatalytically active metal source;
[0045] (iii) adding solution II to solution I under stirring;
[0046] (iv) Adjusting the pH to 2-6 with a pH adjuster.
[0047] In the above-mentioned technical solution of the preparation method, when a quaternary ammonium compound is used, the quaternary ammonium compound can be added to solution I in the form of being dissolved in aqueous solution II, and / or can be added to solution I in the form of being dissolved in water to obtain an aqueous solution of the quaternary ammonium compound. We have not found any obvious difference in this regard.
[0048] The solvent used in the solution I of step (i) is not particularly limited, as long as it can dissolve titanate and silicate and is miscible with water. For example, but not limited to, the solvent used in the solution I of step (i) is a low-carbon alcohol, preferably a C1-C3 alcohol. As a non-limiting example, the low-carbon alcohol can be a monohydric alcohol, a dihydric alcohol or a trihydric alcohol. For example, but not limited to, the low-carbon alcohol is methanol, ethanol, ethylene glycol, n-propanol, isopropanol, 1,2-propylene glycol, 1,3-propylene glycol, etc. However, from the perspective of mass transfer, monohydric alcohols can usually be selected because monohydric alcohols have lower viscosity than dihydric alcohols and trihydric alcohols. Only for year-on-year comparison, ethanol is generally used for low-carbon alcohols in the embodiments and comparative examples.
[0049] In the above-mentioned technical scheme of the preparation method, preferably, in step (i), the weight concentration of TiO2 in solution I is 5-20% by weight of titanate in terms of TiO2, for example but not limited to 6.0%, 7.0%, 8.0%, 9.0%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, etc. For comparison only, the weight concentration of titanium dioxide in solution I in the embodiments and comparative examples is generally 10.0%.
[0050] In the above-mentioned preparation method technical scheme, preferably, the temperature of the hydrolysis reaction in step (2) is 10-50° C. For example, but not limited to, the temperature of the hydrolysis reaction is 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., etc. For comparison only, the temperature of the hydrolysis reaction in step (2) in the embodiments and comparative examples is generally 35° C.
[0051] In the above-mentioned preparation method technical scheme, preferably, the time of the hydrolysis reaction in step (2) is at least 0.5 hours. The longer the hydrolysis reaction time, the better the hydrolysis tendency generated. However, considering the increased effect and time cost, the hydrolysis time we recommend can be 0.5 to 24 hours. For example, but not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, etc. Only for comparison, the time of the hydrolysis reaction in the embodiment of the present invention and the comparative example step (2) is 2 hours.
[0052] In the above-mentioned preparation method technical scheme, preferably, the temperature of the closed heat treatment in step (3) is 120-200° C., for example but not limited to 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., etc., more preferably 150-180° C. For comparison only, the closed heat treatment temperature used in the embodiments is generally 170° C.
[0053] In the above-mentioned preparation method technical scheme, preferably, the time of the closed heat treatment in step (3) is more than 6 hours. The longer the closed heat treatment time is, the better the light deodorization effect tends to be. However, considering the increased deodorization effect and the increased closed heat treatment time cost factors, we recommend a heat treatment time of 6 to 48 hours, such as but not limited to 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 30 hours, 36 hours, 42 hours, etc., and 8 to 12 hours are more recommended. Only for comparison, the closed heat treatment time in the embodiment of the present invention is generally 10 hours.
[0054] After the heat treatment in step (3) and before step (4), a drying step can be added. The drying step can prevent a large amount of gaseous substances from overflowing and causing material splashing at the beginning of the roasting in step (4). There is no special restriction on the drying temperature and drying time. For example, the drying temperature can be 60 to 100°C, such as but not limited to 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, etc. For comparison only, the drying temperature in the embodiments and comparative examples is generally 70°C; for example, the drying time is 0 to 48 hours. For example, but not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, etc. For comparison only, the drying time in the embodiments and comparative examples is generally 6 hours.
[0055] In the above preparation method technical solution, preferably, the calcination temperature in step (4) is 350-650° C., for example but not limited to 400° C., 420° C., 440° C., 460° C., 480° C., 500° C., 520° C., 540° C., 560° C., 580° C., 600° C., 620° C., 640° C., etc., preferably 400-600° C. For comparison only, the calcination temperature in step (4) in the embodiments and comparative examples is generally 500° C.
[0056] In the above preparation method technical solution, preferably, the calcination time of step (4) is 3 to 12 hours, for example but not limited to 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, etc. For comparison only, the calcination time of step (4) in the embodiments and comparative examples is generally 6 hours.
[0057] In the above-mentioned technical solution of the preparation method, the atmosphere for calcination in step (4) is not particularly limited, and those skilled in the art can reasonably select it, and can achieve comparable technical effects without having to make creative efforts. However, from an economic point of view, air calcination is sufficient. For comparison only, the calcination in the specific embodiments of the present invention is carried out in an air atmosphere.
[0058] The third problem to be solved by the present invention is to provide a photocatalytic deodorizing additive composition.
[0059] To solve the third of the above technical problems, the technical solution of the present invention is as follows:
[0060] The photocatalytic deodorizing additive composition comprises, by weight:
[0061] Acrylonitrile polymer, 0.5-18 parts;
[0062] Light deodorizing catalyst, 5-20 parts;
[0063] NaSCN aqueous solution, 100 parts;
[0064] Wherein, in the NaSCN aqueous solution, the weight content of NaSCN is 50-60%;
[0065] The photo-deodorizing catalyst is the photo-deodorizing catalyst described in any one of the technical solutions to the above-mentioned technical problem or the photo-deodorizing catalyst obtained by the preparation method described in any one of the technical solutions to the above-mentioned technical problem.
[0066] In the above-mentioned additive composition technical solution, the acrylonitrile polymer plays the role of a dispersant and a thickener, thereby improving the dispersion stability and suspension stability of the photodeodorizing catalyst. This eliminates the need to introduce other dispersants and thickeners other than the acrylic fiber component, thereby eliminating the adverse effects of dispersants other than the acrylic fiber component on the mechanical properties of acrylic fiber.
[0067] In the above-mentioned technical scheme of additive composition, it is preferred that the acrylonitrile polymer is polyacrylonitrile or an acrylonitrile copolymer having a weight content of acrylonitrile units greater than 85%. For example, but not limited to, the weight content of acrylonitrile units in the acrylonitrile polymer is 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 99%, etc.
[0068] In the above technical solution of the additive composition, the weight content of the acrylonitrile unit in the acrylonitrile copolymer is 85% to 95%, and the weight content of the modified monomer is 5 to 15%.
[0069] In the above-mentioned technical scheme of the additive composition, the modified monomer can be a non-ionic modified monomer (such as methyl acrylate, methyl methacrylate, etc.) and / or an ionic modified monomer (such as sodium acrylate, sodium furanate, sodium methyl methacrylate sulfonate, sodium propylene sulfonate, etc.). For example, the acrylonitrile copolymer composition is based on weight, and the content of acrylonitrile units is 85% to 92% (for example, but not limited to 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%), the content of non-ionic modified monomer units is 8% to 14%, and the content of ionic modified monomer units is 0.1% to 1.0% (for example, but not limited to 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, etc.). Compared with the same period last year, in the acrylonitrile polymers used in the embodiments of the present invention and the comparative examples, the weight content of acrylonitrile units was 91.2%, the content of non-ionic modified monomers (all methyl acrylate) units was 8.1%, and the content of ionic modified monomers (all sodium methyl methacrylate) units was 0.7%.
[0070] In the above-mentioned technical solution of the additive composition, the weight average molecular weight of the acrylonitrile polymer is preferably 40,000 to 100,000 g / mol. For example, but not limited to, the weight average molecular weight of the acrylonitrile polymer is 45,000 g / mol, 50,000 g / mol, 55,000 g / mol, 60,000 g / mol, 65,000 g / mol, 70,000 g / mol, 75,000 g / mol, 80,000 g / mol, 85,000 g / mol, 90,000 g / mol, 95,000 g / mol, etc. For comparison only, the weight average molecular weight of the acrylonitrile polymer used in the embodiments of the present invention and the comparative examples is 68,000 g / mol.
[0071] In the above-mentioned additive composition technical solution, the molecular weight distribution of the acrylonitrile polymer is preferably 2 to 4, for example but not limited to, the molecular weight distribution of the acrylonitrile polymer in the additive composition technical solution is 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, etc. For comparison only, in the embodiment, in the additive composition technical solution, the molecular weight distribution of the acrylonitrile polymer is 2.8.
[0072] In the present invention, the molecular weight distribution adopts the definition in the art, that is, the ratio of the weight average molecular weight to the number average molecular weight.
[0073] As a non-limiting example, in the photocatalytic deodorizing additive composition, the amount of acrylonitrile polymer is 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, etc.
[0074] In the above-mentioned technical solution of the additive composition, those skilled in the art know that in order to increase the suspension stability of the catalyst in the photocatalytic deodorizing additive composition and reduce the adverse effects on acrylic fiber spinning, the smaller the particles of the catalyst, the better.
[0075] In the above-mentioned technical solution of the additive composition, it is preferred that the particle size D99 of the light deodorizing catalyst is 0.5-1 μm. For example, but not limited to, D99 is 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, etc. For comparison only, in the specific embodiment of the present invention, the particle size D99 of the catalyst is 0.8 μm.
[0076] As a non-limiting example, the amount of the photo-deodorizing catalyst in the photo-catalytic deodorizing additive composition is 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, etc. For comparison only, the amount of the photo-deodorizing catalyst in the photo-catalytic deodorizing additive composition described in the embodiments of the present invention and the comparative examples is 13 parts.
[0077] In the technical solution of the above-mentioned photocatalytic deodorizing additive composition, as a non-limiting example, the NaSCN weight content in the NaSCN aqueous solution is 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, etc. Just as an example, the solvent of the acrylonitrile polymer solution is a NaSCN aqueous solution with a NaSCN weight content of 51.3%.
[0078] The fourth technical problem to be solved by the present invention is to provide a method for preparing a photocatalytic deodorizing additive composition.
[0079] To solve the fourth technical problem above, the technical solution of the present invention is as follows:
[0080] The method for preparing the photocatalytic deodorizing additive composition according to any one of the technical solutions to the third technical problem comprises:
[0081] (A) dry-grinding the photo-deodorizing catalyst described in any one of the technical solutions of the above technical problem or the photo-deodorizing catalyst obtained by the preparation method described in any one of the technical solutions of the above technical problem to obtain powder A;
[0082] (B) wet-grinding a wet-grinding raw material comprising the following components by weight until the catalyst particles have a desired particle size:
[0083] 0.5 to 5 parts of the acrylonitrile polymer described in any one of the technical solutions of the third technical problem;
[0084] Powder A, 5-20 parts;
[0085] 100 parts of the NaSCN aqueous solution described in any one of the technical solutions of the above-mentioned technical problem three.
[0086] In the above-mentioned technical solution of the manufacturing method, the mesh size of the material A in step (A) can be selected to be 200 to 500 meshes.
[0087] In the above technical solution, when the amount of material A and / or the amount of acrylonitrile polymer in the wet-grinding raw material of step (B) is higher than the amount described in step (B), the viscosity of the grinding process will be too high, making the grinding operation difficult.
[0088] In the above technical scheme, as a non-limiting example, the amount of powder A in the wet-milled raw material of step (B) is, for example but not limited to, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, etc. For comparison only, the amount of powder A in the embodiment of the present invention and the comparative example is 13 parts.
[0089] In the above-mentioned manufacturing method technical scheme, as a non-limiting example, the amount of acrylonitrile polymer in the wet grinding raw material of step (B) is, for example, but not limited to, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc.), at this time, wet grinding can be carried out smoothly, and the acrylonitrile polymer plays the role of wet grinding dispersant in the wet grinding process, which can improve the wet grinding effect. Only on a year-on-year basis, the number of acrylonitrile polymers used in the wet grinding process in the embodiment is 1 part.
[0090] When the material obtained in the above step (B) requires more acrylonitrile polymer to reach the number of acrylonitrile polymers described in any one of the technical solutions of the above technical problem three, the following steps are also included:
[0091] (C) Supplementing the acrylonitrile polymer in the material obtained in step (B) to the amount of the acrylonitrile polymer described in any one of the technical solutions to the third technical problem.
[0092] The fifth technical problem to be solved by the present invention is to provide a precursor composition of acrylonitrile polymer material.
[0093] To solve the fifth technical problem above, the technical solution of the present invention is as follows:
[0094] The precursor composition of the acrylonitrile polymer material comprises, by weight:
[0095] Acrylonitrile polymer, 10-18 parts;
[0096] Light deodorizing catalyst, greater than 0 and less than 1 part;
[0097] Coupling agent, 0-1 part;
[0098] NaSCN aqueous solution, 100 parts;
[0099] Wherein, the weight content of NaSCN in the NaSCN aqueous solution is 50-60%.
[0100] The photo-deodorizing catalyst is the photo-deodorizing catalyst described in any one of the technical solutions to the above-mentioned technical problem or the photo-deodorizing catalyst obtained by the preparation method described in any one of the technical solutions to the above-mentioned technical problem.
[0101] In the technical solution of the precursor composition of the acrylonitrile polymer material, it is preferred that the acrylonitrile polymer is polyacrylonitrile or an acrylonitrile copolymer having a weight content of acrylonitrile units greater than 85%. For example, but not limited to, the weight content of acrylonitrile units in the acrylonitrile polymer is 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 99%, etc.
[0102] In the technical solution of the precursor composition of the acrylonitrile polymer material, it is preferred that the weight content of the acrylonitrile unit in the acrylonitrile copolymer is 85% to 95%, and the weight content of the modified monomer is 5 to 15%.
[0103] In the technical solution of the precursor composition of the acrylonitrile polymer material, the modified monomer can be a non-ionic modified monomer (such as methyl acrylate, methyl methacrylate, etc.) and / or an ionic modified monomer (such as sodium acrylate, sodium furanate, sodium methacrylic acid, sodium propylene sulfonate, etc.). For example, the acrylonitrile copolymer composition is based on weight, and the content of acrylonitrile units is 85% to 92% (for example, but not limited to 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%), the content of non-ionic modified monomer units is 8% to 14%, and the content of ionic modified monomer units is 0.1% to 1.0% (for example, but not limited to 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, etc.). Compared with the same period last year, in the acrylonitrile polymers used in the embodiments of the present invention and the comparative examples, the weight content of acrylonitrile units was 91.2%, the content of non-ionic modified monomers (all methyl acrylate) units was 8.1%, and the content of ionic modified monomers (all sodium methyl methacrylate) units was 0.7%.
[0104] In the technical solution of the precursor composition of the acrylonitrile polymer material, the weight average molecular weight of the acrylonitrile polymer is preferably 40,000 to 100,000 g / mol. For example, but not limited to, the weight average molecular weight of the acrylonitrile polymer is 45,000 g / mol, 50,000 g / mol, 55,000 g / mol, 60,000 g / mol, 65,000 g / mol, 70,000 g / mol, 75,000 g / mol, 80,000 g / mol, 85,000 g / mol, 90,000 g / mol, 95,000 g / mol, etc. For comparison only, the weight average molecular weight of the acrylonitrile polymer in the embodiments of the present invention and the comparative examples is 68,000 g / mol.
[0105] In the technical solution of the precursor composition of the acrylonitrile polymer material, the molecular weight distribution of the acrylonitrile polymer is preferably 2 to 4, for example but not limited to, the molecular weight distribution of the acrylonitrile polymer in the technical solution of the precursor composition of the acrylonitrile polymer material is 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, etc. For comparison only, in the embodiment, in the technical solution of the precursor composition of the acrylonitrile polymer material, the molecular weight distribution of the acrylonitrile polymer is 2.8.
[0106] As a non-limiting example, in the precursor composition of the acrylonitrile polymer material, the proportion of the acrylonitrile polymer is 10, 11, 12, 13, 14, 15, 16, 17, etc. For comparison only, the proportion of the acrylonitrile polymer in the embodiments of the present invention and the comparative examples is 14.
[0107] In the technical solution of the precursor composition of the acrylonitrile polymer material mentioned above, those skilled in the art know that in order to increase the suspension stability of the catalyst in the precursor composition of the acrylonitrile polymer material, the smaller the catalyst particles, the better. As a non-limiting example only, the particle size D99 of the light deodorization catalyst is 0.5 to 1 μm. For example but not limited to D99 is 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, etc. Only for comparison, in the specific embodiment of the present invention, the catalyst particle size D99 is 0.8 μm.
[0108] As a non-limiting example, the amount of the photo-deodorizing catalyst in the precursor composition of the acrylonitrile polymer material is 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc. For comparison only, the amount of the photo-deodorizing catalyst in the precursor composition embodiment and comparative example of the acrylonitrile polymer material of the present invention is 0.3 part.
[0109] In the technology of the precursor composition of the acrylonitrile polymer material, a coupling agent may be used or not, and comparable technical effects of the present invention can be achieved. However, the use of a coupling agent can further reduce the tendency of the fiber to have poor mechanical properties due to the introduction of a catalyst.
[0110] In the technology of the precursor composition of the acrylonitrile polymer material, when a coupling agent is used, as a non-limiting example, the coupling agent is 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc. For comparison only, when a coupling agent is used in the embodiments, the amount of the coupling agent is 0.3 part.
[0111] In the above-mentioned technology of the precursor composition of the acrylonitrile polymer material, a silane coupling agent is preferred. As non-limiting examples only, the silane coupling agents available from commercial channels include: silane coupling agent KH550 (chemical name: γ-aminopropyltriethoxysilane), silane coupling agent KH560 (chemical name: γ-(2,3-epoxypropoxy)propyltrimethoxysilane), silane coupling agent KH570 (chemical name: γ-(methacryloyloxy)propyltrimethoxysilane), silane coupling agent KH580 (chemical name: γ-mercaptopropyltriethoxysilane), silane coupling agent -KH590 (chemical name: γ-mercaptopropyltrimethoxysilane), silane coupling agent KH602 (chemical name: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane), silane coupling agent KH792 (also known as silane coupling agent KH900) (chemical name: γ-aminoethylaminopropyltrimethoxysilane). For comparison only, the specific embodiments of the present invention generally use the silane coupling agent KH602.
[0112] In the technology of the precursor composition of the acrylonitrile polymer material, as a non-limiting example, the NaSCN aqueous solution has a NaSCN weight content of 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, etc. As an example only, the NaSCN aqueous solution is a NaSCN aqueous solution with a NaSCN weight content of 51.3%.
[0113] There is no special requirement for the preparation method of the precursor composition of the acrylonitrile polymer material of the present invention. According to the understanding of those skilled in the art, it is sufficient to mix uniformly. For comparison only, the preparation method of the precursor composition of the acrylonitrile polymer material in the embodiments of the present invention is obtained by mixing the required acrylonitrile polymer stock solution, the required photocatalytic deodorizing additive composition, the silane coupling agent and the required NaSCN solution.
[0114] The sixth technical problem to be solved by the present invention is the application of light deodorizing catalyst.
[0115] To solve the sixth of the above technical problems, the technical solution of the present invention is as follows:
[0116] The use of the photo-deodorizing catalyst described in any one of the technical solutions of the above technical problems, or the photo-deodorizing catalyst obtained by the preparation method described in any one of the technical solutions of the above technical problems, or the photocatalytic deodorizing additive composition described in any one of the technical solutions of the above technical problems, or the photocatalytic deodorizing additive composition obtained by the manufacturing method described in any one of the technical solutions of the above technical problems, or the precursor composition of the acrylonitrile polymer material described in any one of the technical solutions of the above technical problems, in the production of acrylonitrile polymer fibers or acrylonitrile polymer fibers.
[0117] The key to the present invention is the selection of the photo-deodorizing catalyst, and the specific application method in acrylonitrile polymer fiber can be reasonably selected by those skilled in the art without having to make creative efforts. Acrylonitrile polymer fiber, also known as acrylic fiber, is abbreviated as acrylic fiber.
[0118] The seventh technical problem to be solved by the present invention is to provide a spinning production method for acrylic fiber.
[0119] To solve the seventh technical problem above, the technical solution of the present invention is as follows:
[0120] A spinning production method for acrylic fiber, using the precursor composition described in any one of the technical solutions of the fifth technical problem as a spinning solution, the steps comprising: a. extruding the spinning solution through a spinneret; b. coagulating in a coagulation bath to obtain nascent fibers; c. cold drawing; d. washing; e. hot drawing; f. oiling the fibers; g. drying; and h. heat setting.
[0121] The technical key of the present invention is the photo-deodorizing catalyst, and those skilled in the art can reasonably choose how to use the catalyst in the production of acrylic fiber without having to make creative efforts, and can achieve comparable technical effects.
[0122] In the technical solution of the spinning production method of the acrylic fiber, preferably, the extrusion temperature of the spinneret in step a is 30-80°C, for example but not limited to 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, etc. For comparison only, the extrusion temperature of the spinneret in the embodiment of the present invention and the comparative example is 50°C.
[0123] In the technical scheme of the spinning production method of the acrylic fiber, preferably, the extrusion speed of the spinneret in step a is 10 to 30 m / min. For example, but not limited to, the extrusion speed is 11 m / min, 12 m / min, 13 m / min, 14 m / min, 15 m / min, 16 m / min, 17 m / min, 18 m / min, 19 m / min, 20 m / min, 21 m / min, 22 m / min, 23 m / min, 24 m / sec, 25 m / min, 26 m / min, 27 m / min, 28 m / min, 29 m / min, etc. For comparison only, the extrusion speed in the embodiment and the comparative example is 27 m / min.
[0124] In the technical solution of the spinning production method of the acrylic fiber, preferably, the coagulation bath in step b is a NaSCN aqueous solution, and the NaSCN weight concentration in the coagulation bath is 5-20%. For example, but not limited to, the NaSCN weight concentration in the coagulation bath is 6%, 7, 8, 9, 10, 11, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, etc., more preferably 9-15%. For comparison only, the NaSCN weight concentration in the coagulation bath in the embodiment and the comparative example is 10.6%.
[0125] In the technical solution of the spinning production method of the acrylic fiber, preferably, the temperature of the coagulation bath in step b is 5 to 35° C. For example, but not limited to, the temperature of the coagulation bath is 5° C., 10° C., 11° C., 12° C., 13° C., 14° C., 15° C., 20° C., 25° C., 30° C., etc., more preferably 10 to 15° C. For comparison only, the temperature of the coagulation bath in the embodiment and the comparative example is 12.5° C.
[0126] In the technical solution of the spinning production method of the acrylic fiber, preferably, the cold drafting in step c is water bath cold drafting. For comparison only, the cold drafting in step c in the embodiment and the comparative example is water bath cold drafting.
[0127] In the technical solution of the spinning production method of the acrylic fiber, preferably, the temperature of the cold drawing in step c is 50-90° C., for example, but not limited to, the temperature of the cold drawing is 51° C., 52° C., 53° C., 54° C., 55° C., 56° C., 57° C., 58° C., 59° C., 60° C., 61° C., 62° C., 63° C., 64° C., 65° C., 70° C., 75° C., 80° C., 85° C., etc., more preferably 50-70° C. For comparison only, the temperature of the cold drawing in the embodiment and the comparative example is 58° C.
[0128] In the technical solution of the spinning production method of the acrylic fiber, preferably, the drafting multiple of the cold draft in step c is 1 to 5, for example but not limited to the drafting multiple of the cold draft is 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3, 3.5, 4, 4.5, etc., more preferably 1 to 2. For comparison only, the drafting multiple of the cold draft in the embodiment and the comparative example is 1.62.
[0129] In the technical solution of the spinning production method of the acrylic fiber, preferably, the washing temperature in step d is 40-90° C., for example, but not limited to, the washing temperature is 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55° C., 56, 57, 58, 59, 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., etc., preferably 40-60° C. For comparison only, the washing temperature in the embodiments and comparative examples is 50° C.
[0130] In the technical solution of the spinning production method of the acrylic fiber, preferably, the temperature of the hot drawing in step e is greater than 60°C to 140°C and higher than the cold drawing temperature in step c, for example, but not limited to, the hot drawing temperature is 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115°C, 120°C, 125°C, 130°C, 135°C, etc. For comparison only, the hot drawing temperature in the embodiment and the comparative example is 98°C.
[0131] In the technical solution of the spinning production method of the acrylic fiber, preferably, the hot drawing in step e is water bath hot drawing. For comparison only, the hot drawing in step e of the embodiment and the comparative example is water bath hot drawing.
[0132] In the technical solution of the spinning production method of the acrylic fiber, preferably, the drafting multiple of the hot drafting in step e is 5 to 15 times, for example but not limited to the drafting multiple of the hot drafting is 6, 7, 8, 9, 10, 11, 12, 13, 14, etc. For comparison only, the drafting multiple of the hot drafting in the embodiment and the comparative example is 7.54 times.
[0133] In the technical solution of the spinning production method of the acrylic fiber, preferably, in step f, the fiber oiling rate is 0.05-0.5%, for example, but not limited to, the oiling rate is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc. For comparison only, the oiling rate in the embodiment and the comparative example is 0.3%.
[0134] Those skilled in the art know that the oil absorption rate of a fiber refers to the ratio of the dry weight of the oil-containing agent in the fiber after oiling to the dry weight of the oil-free fiber.
[0135] In the technical solution of the spinning production method of the acrylic fiber, preferably, the drying temperature in step g is 60-150° C. This is for comparison, the same drying conditions are used in the embodiment of the present invention and the comparative example, and a rotary screen dryer is used to sequentially pass through 7 drying zones 1 to 7 for drying, and the drying temperatures in zones 1 to 7 are 145° C., 135° C., 125° C., 115° C., 100° C., 90° C., and 70° C., respectively.
[0136] In the technical solution of the spinning production method of the acrylic fiber, preferably, the heat setting temperature in step h is 110-150° C. For example, but not limited to, the heat setting temperature is 115° C., 120° C., 125° C., 130° C., 135° C., 140° C., 145° C., etc. For comparison only, in the embodiments and comparative examples, the heat setting temperature is 128° C.
[0137] In the technical solution of the spinning production method of the acrylic fiber, the long fiber form can be maintained after step h, or the following step i can be included after step h, or more commonly:
[0138] i. Cut the fibers into short fibers.
[0139] In the technical solution of the spinning production method of the acrylic fiber, the length of the short fibers in step i is preferably 20 to 150 mm, for example but not limited to 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, etc. For comparison only, both the embodiment and the comparative example include step i, and the length of the short fibers is 38 mm.
[0140] In the technical scheme of the spinning production method for obtaining the above-mentioned acrylic fiber, those skilled in the art can reasonably control the single yarn linear density of the acrylic fiber, for example but not limited to the single yarn linear density of 0.5 to 20 dtex, and more specific non-limiting examples of the single yarn linear density are 1 dtex, 1.5 dtex, 2 dtex, 2.5 dtex, 3 dtex, 4 dtex, 5 dtex, 6 dtex, 7 dtex, 8 dtex, 9 dtex, 10 dtex, 12 dtex, 14 dtex, 14 dtex, 16 dtex, 18 dtex and the like.
[0141] Compared with the same period last year, the single fiber linear density of the fibers in the examples and comparative examples was 2.22 dtex.
[0142] The present invention is described in detail below through specific implementation modes and examples. DETAILED DESCRIPTION
[0143] Determination of deodorizing effect:
[0144] The acrylonitrile polymer staple fibers in the examples or comparative examples are first spun into 32S yarns, and then the yarns are woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0145] The above-mentioned grey fabric was tested according to the inspection tube method in the standard JEC301-2013 formulated by the Japan Association for the Evaluation of Functional Textiles (JAFET), with the grey fabric of the comparative example as the blank sample and the odor component used being ammonia. In this standard method, the photocatalytic deodorization effect is expressed by the V (%) value, and the calculation method is:
[0146] V=R L –RB
[0147] Where R L is the reduction rate under clear conditions (%), R B is the dark condition reduction rate (%).
[0148] About mechanical properties determination:
[0149] The mechanical properties of acrylonitrile polymer materials are determined by the tensile test of acrylic fibers. The tensile properties of acrylic fibers are tested in accordance with GB / T 14337-2008 (Test method for tensile properties of chemical staple fibers). The nominal gauge length of the tensile test fiber is 20 mm, the tensile speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0150] [Comparative Example]
[0151] 1. Preparation of photodeodorization catalyst
[0152] Not available.
[0153] 2. Preparation of photocatalytic deodorizing additive composition
[0154] Not available.
[0155] 3. Preparation of precursor composition of acrylonitrile polymer material
[0156] The formula of the precursor composition is: 14 parts of acrylonitrile polymer and 100 parts of a NaSCN aqueous solution with a weight concentration of 51.3%.
[0157] The specific preparation steps of the precursor composition are: take 109.4 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%) and 4.6 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0158] 4. Preparation of acrylic fiber
[0159] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0160] 5. Light deodorization effect and mechanical properties test
[0161] 5.1. Light deodorization effect test
[0162] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0163] The above-mentioned grey cloth was used as a blank sample for the photo-deodorization effect test of Examples 1 to 5, and thus the photocatalytic deodorization effect V was regarded as 0.
[0164] 5.2 Mechanical properties test
[0165] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0166] The average breaking strength is 3.51 cN / dtex, and the average breaking elongation is 38.2%.
[0167] [Example 1]
[0168] 1. Preparation of photodeodorization catalyst
[0169] (1) obtaining a reaction raw material mixture;
[0170] (i) dissolving n-butyl titanate in ethanol to obtain an n-butyl titanate ethanol solution I having a titanium dioxide weight concentration of 10.0%;
[0171] (ii) dissolving ammonium metatungstate in water to obtain an ammonium metatungstate aqueous solution II having a WO3 weight concentration of 1.0%;
[0172] (iii) adding solution II to solution I under stirring, wherein the weight ratio of solution I to solution II is 2;
[0173] (iv) adjusting the pH to 5 with glacial acetic acid;
[0174] (2) hydrolysis reaction was carried out at 35°C with stirring for 2 hours;
[0175] (3) heat treatment at 170°C for 10 hours; then, drying in a drying oven at 70°C for 6 hours;
[0176] (4) Calcination at 500°C for 6 hours in air atmosphere.
[0177] 2. Preparation of photocatalytic deodorizing additive composition
[0178] (A) The catalyst obtained in the above section 1 was crushed by Raymond mill and passed through a 300-mesh sieve to obtain powder A;
[0179] (B) The formula of the wet grinding raw material is: powder A, 13 parts; acrylonitrile polymer, 1 part; NaSCN aqueous solution (the weight concentration of NaSCN in the NaSCN aqueous solution is 51.3%), 100 parts.
[0180] The specific preparation method of the above wet grinding raw material is: 93.2 parts of NaSCN aqueous solution with a weight concentration of 51.3%, 7.8 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN aqueous solution, and the NaSCN weight concentration in the NaSCN aqueous solution is 51.3%) and 13 parts of powder A are mixed.
[0181] The wet-grinded raw materials are wet-grinded until D99 is 0.8 μm to obtain a finished product of a photocatalytic deodorizing additive composition.
[0182] 3. Preparation of precursor composition of acrylonitrile polymer material
[0183] The formula of the precursor composition is: 14 parts of acrylonitrile polymer; 0.3 parts of light deodorizing catalyst; 0.3 parts of silane coupling agent KH602; and 100 parts of NaSCN aqueous solution with a weight concentration of 51.3%.
[0184] The specific preparation steps of the precursor composition are: take 109.2 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%), 2.6 parts of the finished product of the photocatalytic deodorizing additive composition in step 2, 0.3 parts of silane coupling agent KH 602 and 2.5 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0185] 4. Preparation of acrylic fiber
[0186] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0187] 5. Light deodorization effect and mechanical properties test
[0188] 5.1. Light deodorization effect test
[0189] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0190] After testing, the deodorizing effect v is 42%.
[0191] 5.2 Mechanical properties test
[0192] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0193] After testing, the average breaking strength is 2.69 cN / dtex and the average breaking elongation is 26.8%.
[0194] [Example 2]
[0195] 1. Preparation of photodeodorization catalyst
[0196] (1) obtaining a reaction raw material mixture;
[0197] (i) dissolving n-butyl titanate in ethanol to obtain an n-butyl titanate ethanol solution I having a titanium dioxide weight concentration of 10.0%;
[0198] (ii) dissolving ammonium heptamolybdate in water to obtain an ammonium heptamolybdate aqueous solution II having a MoO3 weight concentration of 1.0%;
[0199] (iii) adding solution II to solution I under stirring, wherein the weight ratio of solution I to solution II is 2;
[0200] (iv) adjusting the pH to 5 with glacial acetic acid;
[0201] (2) hydrolysis reaction was carried out at 35°C with stirring for 2 hours;
[0202] (3) heat treatment at 170°C for 10 hours; then, drying in a drying oven at 70°C for 6 hours;
[0203] (4) Calcination at 500°C for 6 hours in air atmosphere.
[0204] 2. Preparation of photocatalytic deodorizing additive composition
[0205] (A) The catalyst obtained in the above section 1 was crushed by Raymond mill and passed through a 300-mesh sieve to obtain powder A;
[0206] (B) The formula of the wet grinding raw material is: powder A, 13 parts; acrylonitrile polymer, 1 part; NaSCN aqueous solution (the weight concentration of NaSCN in the NaSCN aqueous solution is 51.3%), 100 parts.
[0207] The specific preparation method of the above wet grinding raw material is: 93.2 parts of NaSCN aqueous solution with a weight concentration of 51.3%, 7.8 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN aqueous solution, and the NaSCN weight concentration in the NaSCN aqueous solution is 51.3%) and 13 parts of powder A are mixed.
[0208] The wet-grinded raw materials are wet-grinded until D99 is 0.8 μm to obtain a finished product of a photocatalytic deodorizing additive composition.
[0209] 3. Preparation of precursor composition of acrylonitrile polymer material
[0210] The formula of the precursor composition is: 14 parts of acrylonitrile polymer; 0.3 parts of light deodorizing catalyst; 0.3 parts of silane coupling agent KH602; and 100 parts of NaSCN aqueous solution with a weight concentration of 51.3%.
[0211] The specific preparation steps of the precursor composition are: take 109.2 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%), 2.6 parts of the finished product of the photocatalytic deodorizing additive composition in step 2, 0.3 parts of silane coupling agent KH 602 and 2.5 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0212] 4. Preparation of acrylic fiber
[0213] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0214] 5. Light deodorization effect and mechanical properties test
[0215] 5.1. Light deodorization effect test
[0216] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0217] After testing, the deodorizing effect v is 47%.
[0218] 5.2 Mechanical properties test
[0219] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0220] After testing, the average breaking strength is 2.74 cN / dtex and the average breaking elongation is 28.0%.
[0221] [Example 3]
[0222] 1. Preparation of photodeodorization catalyst
[0223] (1) obtaining a reaction raw material mixture;
[0224] (i) dissolving n-butyl titanate in ethanol to obtain an n-butyl titanate ethanol solution I having a titanium dioxide weight concentration of 10.0%;
[0225] (ii) dissolving ammonium metatungstate and ammonium heptamolybdate in water to obtain an ammonium metatungstate-ammonium heptamolybdate mixed aqueous solution II having a WO3 weight concentration of 0.80% and a MoO3 weight concentration of 0.20%;
[0226] (iii) adding solution II to solution I under stirring, wherein the weight ratio of solution I to solution II is 2;
[0227] (iv) adjusting the pH to 5 with glacial acetic acid;
[0228] (2) hydrolysis reaction was carried out at 35°C with stirring for 2 hours;
[0229] (3) heat treatment at 170°C for 10 hours; then, drying in a drying oven at 70°C for 6 hours;
[0230] (4) Calcination at 500°C for 6 hours in air atmosphere.
[0231] 2. Preparation of photocatalytic deodorizing additive composition
[0232] (A) The catalyst obtained in the above section 1 was crushed by Raymond mill and passed through a 300-mesh sieve to obtain powder A;
[0233] (B) The formula of the wet grinding raw material is: powder A, 13 parts; acrylonitrile polymer, 1 part; NaSCN aqueous solution (the weight concentration of NaSCN in the NaSCN aqueous solution is 51.3%), 100 parts.
[0234] The specific preparation method of the above wet grinding raw material is: 93.2 parts of NaSCN aqueous solution with a weight concentration of 51.3%, 7.8 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN aqueous solution, and the NaSCN weight concentration in the NaSCN aqueous solution is 51.3%) and 13 parts of powder A are mixed.
[0235] The wet-grinded raw materials are wet-grinded until D99 is 0.8 μm to obtain a finished product of a photocatalytic deodorizing additive composition.
[0236] 3. Preparation of precursor composition of acrylonitrile polymer material
[0237] The formula of the precursor composition is: 14 parts of acrylonitrile polymer; 0.3 parts of light deodorizing catalyst; 0.3 parts of silane coupling agent KH602; and 100 parts of NaSCN aqueous solution with a weight concentration of 51.3%.
[0238] The specific preparation steps of the precursor composition are: take 109.2 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%), 2.6 parts of the finished product of the photocatalytic deodorizing additive composition in step 2, 0.3 parts of silane coupling agent KH 602 and 2.5 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0239] 4. Preparation of acrylic fiber
[0240] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0241] 5. Light deodorization effect and mechanical properties test
[0242] 5.1. Light deodorization effect test
[0243] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0244] After testing, the deodorizing effect v is 63%.
[0245] 5.2 Mechanical properties test
[0246] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0247] After testing, the average breaking strength is 2.65 cN / dtex and the average breaking elongation is 27.3%.
[0248] [Example 4]
[0249] 1. Preparation of photodeodorization catalyst
[0250] (1) obtaining a reaction raw material mixture;
[0251] (i) dissolving n-butyl titanate and ethyl silicate in ethanol to obtain an n-butyl titanate-ethyl silicate ethanol solution I having a titanium dioxide concentration of 10.0% by weight and a silicon dioxide concentration of 0.04% by weight;
[0252] (ii) dissolving ammonium metatungstate and ammonium heptamolybdate in water to obtain an ammonium metatungstate-ammonium heptamolybdate mixed aqueous solution II having a WO3 weight concentration of 0.80% and a MoO3 weight concentration of 0.20%;
[0253] (iii) adding solution II to solution I under stirring, wherein the weight ratio of solution I to solution II is 2;
[0254] (iv) adjusting the pH to 5 with glacial acetic acid;
[0255] (2) hydrolysis reaction was carried out at 35°C with stirring for 2 hours;
[0256] (3) heat treatment at 170°C for 10 hours; then, drying in a drying oven at 70°C for 6 hours;
[0257] (4) Calcination at 500°C for 6 hours in air atmosphere.
[0258] 2. Preparation of photocatalytic deodorizing additive composition
[0259] (A) The catalyst obtained in the above section 1 was crushed by Raymond mill and passed through a 300-mesh sieve to obtain powder A;
[0260] (B) The formula of the wet grinding raw material is: powder A, 13 parts; acrylonitrile polymer, 1 part; NaSCN aqueous solution (the weight concentration of NaSCN in the NaSCN aqueous solution is 51.3%), 100 parts.
[0261] The specific preparation method of the above wet grinding raw material is: 93.2 parts of NaSCN aqueous solution with a weight concentration of 51.3%, 7.8 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN aqueous solution, and the NaSCN weight concentration in the NaSCN aqueous solution is 51.3%) and 13 parts of powder A are mixed.
[0262] The wet-grinded raw materials are wet-grinded until D99 is 0.8 μm to obtain a finished product of a photocatalytic deodorizing additive composition.
[0263] 3. Preparation of precursor composition of acrylonitrile polymer material
[0264] The formula of the precursor composition is: 14 parts of acrylonitrile polymer; 0.3 parts of light deodorizing catalyst; 0.3 parts of silane coupling agent KH602; and 100 parts of NaSCN aqueous solution with a weight concentration of 51.3%.
[0265] The specific preparation steps of the precursor composition are: take 109.2 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%), 2.6 parts of the finished product of the photocatalytic deodorizing additive composition in step 2, 0.3 parts of silane coupling agent KH 602 and 2.5 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0266] 4. Preparation of acrylic fiber
[0267] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0268] 5. Light deodorization effect and mechanical properties test
[0269] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0270] After testing, the deodorizing effect v is 61%.
[0271] 5.2 Mechanical properties test
[0272] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0273] After testing, the average breaking strength is 3.27 cN / dtex and the average breaking elongation is 35.5%.
[0274] [Example 5]
[0275] 1. Preparation of photodeodorization catalyst
[0276] (1) obtaining a reaction raw material mixture;
[0277] (i) dissolving n-butyl titanate and ethyl silicate in ethanol to obtain an n-butyl titanate-ethyl silicate ethanol solution I having a titanium dioxide concentration of 10.0% by weight and a silicon dioxide concentration of 0.04% by weight;
[0278] (ii) dissolving ammonium metatungstate, ammonium heptamolybdate and tetraethylammonium bromide in water to obtain a mixed aqueous solution II of ammonium metatungstate-ammonium heptamolybdate-tetraethylammonium bromide having a weight concentration of 0.80% WO3, a weight concentration of 0.20% MoO3 and a weight concentration of 2.0% tetraethylammonium bromide;
[0279] (iii) adding solution II to solution I under stirring, wherein the weight ratio of solution I to solution II is 2;
[0280] (iv) adjusting the pH to 5 with glacial acetic acid;
[0281] (2) hydrolysis reaction was carried out at 35°C with stirring for 2 hours;
[0282] (3) heat treatment at 170°C for 10 hours; then, drying in a drying oven at 70°C for 6 hours;
[0283] (4) Calcination at 500°C for 6 hours in air atmosphere.
[0284] 2. Preparation of photocatalytic deodorizing additive composition
[0285] (A) The catalyst obtained in the above section 1 was crushed by Raymond mill and passed through a 300-mesh sieve to obtain powder A;
[0286] (B) The formula of the wet grinding raw material is: powder A, 13 parts; acrylonitrile polymer, 1 part; NaSCN aqueous solution (the weight concentration of NaSCN in the NaSCN aqueous solution is 51.3%), 100 parts.
[0287] The specific preparation method of the above wet grinding raw material is: 93.2 parts of NaSCN aqueous solution with a weight concentration of 51.3%, 7.8 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN aqueous solution, and the NaSCN weight concentration in the NaSCN aqueous solution is 51.3%) and 13 parts of powder A are mixed.
[0288] The wet-grinded raw materials are wet-grinded until D99 is 0.8 μm to obtain a finished product of a photocatalytic deodorizing additive composition.
[0289] 3. Preparation of precursor composition of acrylonitrile polymer material
[0290] The formula of the precursor composition is: 14 parts of acrylonitrile polymer; 0.3 parts of light deodorizing catalyst; 0.3 parts of silane coupling agent KH602; and 100 parts of NaSCN aqueous solution with a weight concentration of 51.3%.
[0291] The specific preparation steps of the precursor composition are: take 109.2 parts of acrylonitrile polymer stock solution (the weight content of acrylonitrile polymer in the acrylonitrile polymer stock solution is 12.8%, the solvent is NaSCN solution, and the weight content of NaSCN in the NaSCN solution is 51.3%), 2.6 parts of the finished product of the photocatalytic deodorizing additive composition in step 2, 0.3 parts of silane coupling agent KH 602 and 2.5 parts of NaSCN solution with a NaSCN weight content of 51.3%, and mix them evenly.
[0292] 4. Preparation of acrylic fiber
[0293] The precursor composition in Section 3 is used as the spinning solution to produce 2.22 dtex acrylic fiber. The steps are as follows: a. The spinning solution is extruded through a spinneret; b. The primary fibers are coagulated in a coagulation bath; c. Cold drawing; d. Water washing; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting; i. Cutting the fibers into short fibers. The temperature of spinneret extrusion in step a is 50 ℃, and the speed of spinneret extrusion is 27 m / min; in step b, the coagulation bath is a NaSCN aqueous solution, the NaSCN weight concentration in the coagulation bath is 10.6%, and the temperature of the coagulation bath is 12.5 ℃; in step c, cold drawing is water bath cold drawing, the temperature of cold drawing is 58 ℃, and the drafting multiple of cold drawing is 1.62; in step d, the temperature of washing is 50 ℃; in step e, the temperature of hot drawing is 98 ℃, the hot drawing is water bath hot drawing, and the drafting multiple of hot drawing is 7.54 times; in step f, the fiber oiling rate is 0.3%; in step g, a round net dryer is used to dry in 7 drying zones in 1 to 7 zones in sequence, and the drying temperatures in 1 to 7 zones are 145 ℃, 135 ℃, 125 ℃, 115 ℃, 100 ℃, 90 ℃, and 70 ℃ respectively; in step h, the temperature of heat setting is 128 ℃; in step i, the staple length is 38 mm.
[0294] 5. Light deodorization effect and mechanical properties test
[0295] 5.1. Light deodorization effect test
[0296] The short fibers in Section 4 above are spun into 32S yarns, which are then woven into grey cloths with the following specifications: warp density 555 / 10cm, weft density 268 / 10cm, width 148cm, grey cloth weight 155g / m 2 .
[0297] After testing, the deodorizing effect v is 79%.
[0298] 5.2 Mechanical properties test
[0299] The acrylic fiber in Section 4 is used as the sample for the draft test. The draft properties of acrylic fiber are tested in accordance with GB / T14337-2008 (Test method for draft properties of chemical staple fibers). The nominal gauge length of the draft test fiber is 20 mm, the drafting speed is 20 mm / min, and the test is carried out in the "dry test" mode specified in Section 7.2 of the standard.
[0300] After testing, the average breaking strength is 3.30 cN / dtex and the average breaking elongation is 32.6%.
Claims
1. A photocatalytic deodorizing additive composition, comprising, by weight: Acrylonitrile polymer, 0.5-18 parts; Light deodorizing catalyst, 5-20 parts; NaSCN aqueous solution, 100 parts; Wherein, in the NaSCN aqueous solution, the weight content of NaSCN is 50-60%; The characteristic is that the light deodorizing catalyst comprises the following components by weight: The first component: 100 parts; the second component: part a; the third component: part b; The first component is TiO2, the second component is a photocatalytically active metal oxide, and the third component is SiO2; Wherein, a=0.01-10, b=0-0.5; and the second component includes both WO3 and MoO3. Preferably, the weight ratio of MoO3 to WO3 is 0.05-1. More preferably, the weight ratio of MoO3 to WO3 is 0.1-0.
5.
2. The method for preparing the photocatalytic deodorizing additive composition according to claim 1, comprising: (A) dry-grinding the photo-deodorizing catalyst to obtain powder A; (B) wet-grinding a wet-grinding raw material comprising the following components by weight until the catalyst particles have a desired particle size: Acrylonitrile polymer, 0.5-5 parts; Powder A, 5-20 parts; NaSCN aqueous solution, 100 parts. The mesh size of the powder A is preferably 200 to 500 mesh.
3. The manufacturing method according to claim 2, characterized in that When the material obtained in step (B) requires more acrylonitrile polymer to reach the amount of acrylonitrile polymer in the photocatalytic deodorizing additive composition of claim 1, the following steps are also included: (C) Supplementing the acrylonitrile polymer in the material obtained in step (B) to the amount of the acrylonitrile polymer as claimed in claim 181.
4. A precursor composition of an acrylonitrile polymer material, comprising, by weight: Acrylonitrile polymer, 10-18 parts; Light deodorizing catalyst, greater than 0 and less than 1 part; Coupling agent, 0-1 part; NaSCN aqueous solution, 100 parts; In the NaSCN aqueous solution, the NaSCN weight content is 50-60%; The light deodorizing catalyst comprises the following components by weight: The first component: 100 parts; the second component: part a; the third component: part b; The first component is TiO2, the second component is a photocatalytically active metal oxide, and the third component is SiO2; Wherein, a=0.01-10, b=0-0.5; and the second component includes both WO3 and MoO3. Preferably, the weight ratio of MoO3 to WO3 is 0.05-1. More preferably, the weight ratio of MoO3 to WO3 is 0.1-0.
5.
5. The precursor composition of the acrylonitrile polymer material according to claim 4, characterized in that The acrylonitrile polymer is polyacrylonitrile or an acrylonitrile copolymer with an acrylonitrile weight content greater than 85%; and / or the weight average molecular weight of the acrylonitrile polymer is 40,000 to 100,000 g / mol.
6. The precursor composition of the acrylonitrile polymer material according to claim 4, characterized in that The particle size D99 of the light deodorizing catalyst is 0.5 to 1 μm.
7. The precursor composition of the acrylonitrile polymer material according to claim 4, characterized in that The coupling agent is a silane coupling agent.
8. Use of the photocatalytic deodorizing additive composition according to claim 1, the photocatalytic deodorizing additive composition obtained by the manufacturing method according to any one of claims 2 to 3, or the precursor composition of the acrylonitrile polymer material according to any one of claims 4 to 7 in the production of acrylonitrile polymer fibers or acrylonitrile polymer fibers.
9. A spinning method for producing acrylic fiber, using the precursor composition according to any one of claims 4 to 7 as a spinning solution, the steps comprising: a. The spinning solution is extruded through the spinneret; b. Coagulation in a coagulation bath to obtain primary fibers; c. Cold drawing; d. Wash with water; e. Hot drawing; f. Oiling the fibers; g. Drying; h. Heat setting.
